1989
DOI: 10.4049/jimmunol.142.12.4428
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial properties of eosinophil major basic protein and eosinophil cationic protein.

Abstract: We examined the bactericidal activity of two proteins that are abundant in the cytoplasmic granules of human eosinophils, major basic protein (MBP) and eosinophil cationic protein (ECP). Unlike the human neutrophil's peptide defensins, both MBP and ECP killed stationary phase Staphylococcus aureus 502A in a simple nutrient-free buffer solution. Although MBP also killed Escherichia coli ML-35 with considerable efficacy under these experimental conditions, the in vitro activity of ECP against E. coli was conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 257 publications
(9 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…The EoE activity did not seem to directly affect a load of bacteria in EoE. However, eosinophils possess extracellular DNA traps and numerous anti-microbial properties with the release of defensins (63)(64)(65). The microbiota of untreated EoE subjects showed a shift from a mostly Gram (+) population to an increase in Gram (−) bacteria similar to what has been described in GERD (49).…”
Section: Oesophageal Microbiota In Eoe the Main Findingssupporting
confidence: 53%
“…The EoE activity did not seem to directly affect a load of bacteria in EoE. However, eosinophils possess extracellular DNA traps and numerous anti-microbial properties with the release of defensins (63)(64)(65). The microbiota of untreated EoE subjects showed a shift from a mostly Gram (+) population to an increase in Gram (−) bacteria similar to what has been described in GERD (49).…”
Section: Oesophageal Microbiota In Eoe the Main Findingssupporting
confidence: 53%
“…Eosinophils produce and store many biologically active molecules in their granules, including eosinophil peroxidase (EPX), eosinophil cationic protein (ECP), eosinophil major basic protein 1 (eMBP1), major basic protein 2, and numerous cytokines, including TGF‐ß (Table S2 ). 12 , 13 , 14 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 In the setting of massive and persistent eosinophil activation, eosinophil‐derived (toxic) substances can cause substantial changes in the local microenvironment, resulting in organ damage, often in association with local inflammation, cytotoxicity, thromboembolic complications, and/or fibrosis. 1 , 2 , 3 , 12 , 13 , 14 , 42 , 43 , 44 In patients with tissue HE and persistent eosinophil activation, marked deposition of eosinophil granule proteins, including eMBP1 and EPX, is usually found although staining for these eosinophil‐derived proteins is not standardized or available in most centers.…”
Section: Eosinophil Biology and Normal Laboratory Valuesmentioning
confidence: 99%
“…The results revealed that Ds-DbRCaG-07-Rga1p, Ds-DbRCaG-09-Rga9p, Ds-DbRCaG-10-Rga13p, and Ds-DbRCaG-11-Rga15p are basic proteins. Eosinophil protein (MBP) has antibacterial activity against microbes ( Lehrer et al., 1989 ). Arginine has an essential role in immune mechanisms and in combating pathogen attacks.…”
Section: Discussionmentioning
confidence: 99%